Theorizing and Documenting the Spread of Teach For All and its Impact on Global Education Reform - Straubhaar, Rolf; Friedrich, Daniel (Education Policy Analysis Archives, 2015)
Within global education policy, the role of multilateral agencies in pushing cross-national policy borrowing is increasingly being complemented by efforts from private international networks within civil society, such as Teach For All. This introductory article summarizes the scarce extant literature on Teach For All, highlighting the contributions to this growing area of inquiry within this special issue. Especially provocative and fruitful lines of further inquiry surrounding Teach For All and similar policy networks are also highlighted and explored.